2020
DOI: 10.1038/s41598-020-76604-2
|View full text |Cite
|
Sign up to set email alerts
|

Coral cover surveys corroborate predictions on reef adaptive potential to thermal stress

Abstract: As anomalous heat waves are causing the widespread decline of coral reefs worldwide, there is an urgent need to identify coral populations tolerant to thermal stress. Heat stress adaptive potential is the degree of tolerance expected from evolutionary processes and, for a given reef, depends on the arrival of propagules from reefs exposed to recurrent thermal stress. For this reason, assessing spatial patterns of thermal adaptation and reef connectivity is of paramount importance to inform conservation strateg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Over the last decade, the combination of field survey records with remote sensed data for sea surface temperature has become one of the major tools used to measure coral decline associated with heat stress. Multiple studies have shown associations between heat stress events and coral cover decline at both local (Head et al, 2019;Babcock et al, 2020;Selmoni et al, 2020a) and global scales (Selig et al, 2012). In other studies, the bleaching intensity metric was found to be positively associated with heat stress on the Australian Great Barrier Reef (Hughes et al, 2018;Hughes et al, 2019), as well as across larger spatial scales (for instance, the Indo-Pacific region; Sully et al, 2019;McClanahan et al, 2020a).…”
Section: Introductionmentioning
confidence: 96%
“…Over the last decade, the combination of field survey records with remote sensed data for sea surface temperature has become one of the major tools used to measure coral decline associated with heat stress. Multiple studies have shown associations between heat stress events and coral cover decline at both local (Head et al, 2019;Babcock et al, 2020;Selmoni et al, 2020a) and global scales (Selig et al, 2012). In other studies, the bleaching intensity metric was found to be positively associated with heat stress on the Australian Great Barrier Reef (Hughes et al, 2018;Hughes et al, 2019), as well as across larger spatial scales (for instance, the Indo-Pacific region; Sully et al, 2019;McClanahan et al, 2020a).…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies on coral evolutionary adaptive potential suggest that reef conservation efforts should be oriented toward reefs exposed to recurrent stress, as these might be the sources for adapted corals in the years to come (Matz et al, 2020; Selmoni et al, 2020a). As coral taxa are likely to have different potentials for adaptation (Darling et al, 2012; Guest et al, 2012; McClanahan et al, 2020), the effectiveness of such conservation strategies will also depend on the community structure of the reefs.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, the combination of field survey records with remote sensed data for sea surface temperature has become one of the main tools used to measure coral decline driven by heat stress. Multiple studies have shown associations between heat stress events and coral cover decline both at local (Head et al, 2019; Babcock et al, 2020; Selmoni et al, 2020a) and global scales (Selig et al, 2012). In other studies, the metric of bleaching intensity was found to be positively associated with heat stress on the Australian Great Barrier Reef (Hughes et al, 2018, 2019), as well as across larger spatial scales (for instance, the Indo-Pacific region; (Sully et al, 2019; McClanahan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations